Dolphins - Simon, Seymour 1931- (Smithsonian, 2009)
Friendly and fascinating, dolphins are one of nature's most intelligent animals. Award-winning science writer Seymour Simon has teamed up with the Smithsonian Institution to give you an expert view of these clever, curious, and mischievous mammals in a full-color photographic introduction